2019
DOI: 10.1111/1759-7714.12960
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of adjuvant therapy in T4 non‐small cell lung cancer: An inverse probability of treatment weighting analysis

Abstract: Background According to the current clinical guidelines, chemoradiotherapy is considered the standard treatment for locally advanced non‐small cell lung cancer (NSCLC). We analyzed the prognostic effect of adjuvant chemotherapy (ACT) in resected patients using the new eighth tumor node metastasis (TNM) staging systems based on the Surveillance, Epidemiology and End Results database. Methods We identified 3008 patients with stage IIIA NSCLC (T4N0M0) who underwent subloba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…However, while we focused on pT4 patients in the present study, they examined cT4 patients. Song et al 18 reported a five-year survival rate of 51.1% in patients with T4 tumors, which was similar to our study. Moreover, they did not exclude non-size-based T4 patients or patients who had received neoadjuvant therapy while achieving this survival result.…”
Section: Discussionsupporting
confidence: 92%
“…However, while we focused on pT4 patients in the present study, they examined cT4 patients. Song et al 18 reported a five-year survival rate of 51.1% in patients with T4 tumors, which was similar to our study. Moreover, they did not exclude non-size-based T4 patients or patients who had received neoadjuvant therapy while achieving this survival result.…”
Section: Discussionsupporting
confidence: 92%